The intraclonal polymorphyism of the antartic ciliate Euplotes focardii. - VALBONESI A; AND LUPORINI P.; FELICI, Alberto (1995)
the intraclonal polymorphyism of the antartia ciliate Euplotes focardii, included the biochemical aspects were investigated; somo pheromones were isolated and partially characterized by HPLC and their mechanism of action studied